Decolonial Pedagogies and Critical Intersectional Perspective: Contemporary Reflections - VISOTSKY-HASRUN, Jessica; REYES-SERNA, José (Utopía y Praxis Latinoamericana, 2025)
In this article, we share some reflections emanating from our educational practices and research in Latin America and France. We aim to contribute to the understanding of Freirean thought in its uniqueness regarding the decolonial perspective by highlighting the pioneering reflections on the links between education and coloniality in the 1960s and 1970s in Latin America. To this end, we revisit the Brazilian educator’s reflections and his dialogues with the work of Frantz Fanon. We reflect on the contemporary context in which we inscribe our practices and the urgency of a decolonizing pedagogy. Finally, we contribute to reflections on a present-day movement in popular education, which has been challenged by the intersectional perspective, suggesting that we find ourselves in a context of a new refoundation of this movement.